How the Italian Nursing students deal the pandemic Covid-19 condition: Covid-19 and nursing student perception - Vitale, Elsa; Moretti, Biagio; Noternicola, Angela; Covelli, Ilaria (Acta Biomedica Atenei Parmensis, 2020)
Background and Aim of the work: Since December 2019, a new infectious disease known as Coronavirus disease (Covid-19) has rapidly spread globally until it has been declared a pandemic by the World Health Organization. At the same time, if we consider the University context, there is little attention paid during basic nursing education to emergency response, and faculty members report feeling poorly prepared to teach students about this topic. The present study aims to investigate how the Covid-19 pandemic condition influenced the psychological well-being of the Italian nursing students. Methods: An online questionnaire was administered to Italian nursing students which contains two parts: a demographic section and the assessment to the psychological well-being nursing student with the Impact of Event Scale-Revised and the Patient Health Questionnaire-9. Results: Given the emergency health situation from Covid-19, our initial concern was to find a large number of students with difficulties in mentally processing this situation even with problems such as depression, as their future profession is heavily involved in the management of this pandemic. Fortunately our results have denied our initial hypothesis since both the impact management levels of the event, assessed with the IES-R scale, and the depression levels, assessed with the PHQ-9 recorded values ​​that were almost normal. Conclusions: Nursing students are better able to face the situation since they find themselves in the role of spectators and not in the role of actors in the care of patients with Covid-19. If the training ameliorates psychological well being, therefore, it is necessary to provide and preserve nurses expertise to encourage teaching in nursing degree courses on maxi emergencies to prepare future nurses to face them adequately.